The Levels of Readiness of Services Providing through the Digital Personnel in Local Administrative Organizations (LAOs): A Case Study of Local Administrative Organizations in Na Dun, Mahasarakham - Prommachot, Narawich; Zumitzavan, Vissanu (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were: (1) to examine digital service provision by personnel in local administrative organizations, and (2) to analyze the level of readiness for digital service delivery among personnel in local administrative organizations in Nadun District, Maha Sarakham Province. This study employed a quantitative research approach. The sample consisted of 290 administrators, civil servants, employees, and workers from nine local administrative organizations in Nadun District, Maha Sarakham Province. The research instrument was a questionnaire. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics, namely Pearson’s correlation coefficient and multiple regression analysis. The results revealed that, regarding the first objective, the overall level of digital service provision by personnel in local administrative organizations was at a high level. Among the dimensions, digital service delivery had the highest mean score, followed by digital service personnel, while digital infrastructure had the lowest mean score. Regarding the second objective, the overall level of readiness for digital service delivery was also at a high level. Hypothesis testing indicated that factors significantly affecting the level of readiness for digital service delivery at the .05 level were budget allocation (Beta = 0.759), age (Beta = 0.284), and the number of training sessions attended per year (Beta = 0.150), respectively. Based on the findings, it is recommended that local administrative organizations prioritize budget allocation for the development of adequate and modern digital infrastructure, along with continuous capacity building and training for personnel, in order to enhance the efficiency and sustainability of digital service delivery